2011
DOI: 10.1002/bmc.1712
|View full text |Cite
|
Sign up to set email alerts
|

Determination and pharmacokinetics of [6]‐gingerol in mouse plasma by liquid chromatography–tandem mass spectrometry

Abstract: This study describes the development of a rapid and sensitive high-performance liquid chromatography-electrospray ionization tandem mass spectrometry (LC-MS/MS) assay for the quantification of [6]-gingerol in mouse plasma and application to a pharmacokinetic study after dose ranging in mice. The assay involved a protein precipitation step with acetonitrile and an isocratic elution using a mobile phase consisting of acetonitrile and water containing 0.1% formic acid (80:20 v/v). The multiple reaction monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The pharmacokinetics of 6-gingerol in mice, rats, and humans have been examined by different research groups. However, the metabolic fate of 6-gingerol, especially in cancer cells and in mice, is still unclear. Nakazawa and co-workers orally administrated 6-gingerol to rats and found that it could be converted to one major metabolite, 6-gingerol-4′-O-β-glucuronide, in bile and six other minor metabolites in urine .…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacokinetics of 6-gingerol in mice, rats, and humans have been examined by different research groups. However, the metabolic fate of 6-gingerol, especially in cancer cells and in mice, is still unclear. Nakazawa and co-workers orally administrated 6-gingerol to rats and found that it could be converted to one major metabolite, 6-gingerol-4′-O-β-glucuronide, in bile and six other minor metabolites in urine .…”
Section: Introductionmentioning
confidence: 99%
“…injection), and blood was collected by cardiac puncture in EDTA-containing tubes. The resulting blood samples (n = 3 animals/time point) were kept on ice, and the plasma obtained by centrifugation at 2000× g was stored at -80 • C until the evaluation of the free 6-gingerol levels was conducted using a method adapted from [33] as described below at the Section "Samples preparation for measurement of free 6-gingerol".…”
Section: Measurement Of the Free 6-gingerol Levels In The Plasma And ...mentioning
confidence: 99%
“…Accurately weighted tissue samples (<200 mg) were homogenized in 200 µL of saline buffer on ice. After this, 10 µL of internal standard (IS) nonivamide 5 µg/mL in acetonitrile and 790 µL of acetonitrile or 390 µL of acetonitrile for 100 µL of plasma were added to each sample (homogenized tissue or plasma) [33]. The samples were vigorously vortexed and centrifuged at 13,500× g for 15 min.…”
Section: Sample Preparation For the Measurement Of Free 6-gingerolmentioning
confidence: 99%
“…Gingerol is the major pungent, nonvolatile, phenolic component of ginger. The herb Zingiber officinale is used to disperse bio-energy Qi , keep Qi in motion and assist in regulating blood circulation; this is the reason for the interdependence between Yin and Yan g [9]. Previous studies have revealed that Ziziphus jujube contains various constituents including triterpenic acids, phenolic acids, and polysaccharides, which may also possess bioactivity [10].…”
Section: Introductionmentioning
confidence: 99%